2011
DOI: 10.4236/jct.2011.23058
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase Therapy in a Murine Hepatitis-Associated Injury

Abstract: We aim to test the hypothesis that Con A-induced hepatitis and cell death can be prevented by the administration of the MnSOD mimetic MnTBAP. Male C57 mice were divided into 3 groups, 1) pretreated with MnTBAP (30 mg/kg) for 2 days and then Concanavalin A (Con A) (15 mg/kg); 2) pretreated with saline for 2 days and then Con A (15 mg/kg); 3) was the control treated with saline for 3 days. Extensive hepatic necrosis, with a significant increase in apoptosis, lipid peroxidation and decreased MnSOD enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The hepatocyte protection by BRB extracts preserving MnSOD in Con A challenged liver is supported by the following observations, 1) an increase in the intracellular steady-state production of H 2 O 2 by MnSOD can protect against tumor necrosis factor induced apoptosis 27 ; 2) overexpression of MnSOD inhibited IFN-γ-mediated ROS accumulation and rescued cells from necroptosis 28 ; 3) in our previous study, we have found that supplementation with a MnSOD mimic-MnTBAP-can also protect the hepatocytes from Con A induced hepatitis 29 ; 4) in the current in vitro data, supplementation with a MnSOD mimic-MnTBAP-can also protect the hepatocytes, while abolishing the MnSOD activity by KCN cannot protect the liver of animals pretreated with BRB.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The hepatocyte protection by BRB extracts preserving MnSOD in Con A challenged liver is supported by the following observations, 1) an increase in the intracellular steady-state production of H 2 O 2 by MnSOD can protect against tumor necrosis factor induced apoptosis 27 ; 2) overexpression of MnSOD inhibited IFN-γ-mediated ROS accumulation and rescued cells from necroptosis 28 ; 3) in our previous study, we have found that supplementation with a MnSOD mimic-MnTBAP-can also protect the hepatocytes from Con A induced hepatitis 29 ; 4) in the current in vitro data, supplementation with a MnSOD mimic-MnTBAP-can also protect the hepatocytes, while abolishing the MnSOD activity by KCN cannot protect the liver of animals pretreated with BRB.…”
Section: Discussionmentioning
confidence: 81%
“…16, 29 Briefly, a colorimetric assay is done by measuring the a water soluble formazan dye, which produced by the reaction between WST-1 and superoxide anion (O 2 − ). The rate of the reduction with O 2 − was linearly related to the xanthine oxidase activity and is inhibited by SOD.…”
Section: Methodsmentioning
confidence: 99%